The Reliability and Validity of an Instrument to Evaluate the Implementation of Professional Learning Communities (PLC) - Thiru Kali Thevi Jayaraman; Nor Hasnida Bt Che Md Ghazali (International Journal of Educational Research Excellence, 2023)
The implementation of Profesional Learning Communities (PLC) among secondary school teachers can enhance school capacity and excellence. To assess the execution of PLC, a reliable and valid instrument is necessary. This research aimed to develop and validate such an instrument, which was distributed to 69 secondary school teachers in the form of a questionnaire. The Context, Input, Process and Product (CIPP) Evaluation Model, established by Daniel Stufflebeam, served as the foundation for the instrument. The content validity of the instrument was examined by experts, while the construct validity was assessed using internal consistency reliability or Cronbach Alpha. The pilot study findings suggest that the instrument is both reliable and valid, with 87 out of 91 items retained.